Back to the roots of internal credit risk models: Does risk explain why banks' risk-weighted asset levels converge over time? - Victoria Böhnke; Steven Ongena; Florentina Paraschiv; Endre J. Reite (Deutsche Bundesbank, 2024)
The internal ratings-based (IRB) approach maps bank risk profiles more adequately than the standardized approach. After switching to IRB, banks' risk-weighted asset (RWA) densities are thus expected to diverge, especially across countries with different supervisory strictness and risk levels. However, when examining 52 listed banks headquartered in 14 European countries that adopted the IRB approach, we observe a downward convergence of their RWA densities over time. We test whether this convergence can be entirely explained by differences in the size of the banks, loss levels, country risk, and/or time of IRB implementation. Our findings indicate that this is not the case. Whereas banks in high-risk countries with less strict regulation and/or supervision, reduce their RWA densities, banks elsewhere increase theirs. Especially for banks in high-risk countries, RWA densities seem to underestimate banks' economic risk. Hence, the IRB approach enables regulatory arbitrage, whereby authorities may only enforce strict supervision on capital requirements if they do not jeopardize bank existence.
Keywords: G21; G28; 330; Capital regulation; credit risk; internal ratings-based approach; regulatory arbitrage; risk-weighted assets